Study on the factors affecting alkalis release from aggregates into ASR - Soares, D. (2017)
Alkaline minerals, like feldspars and micas, present in aggregates can release alkalis with time for concrete pore solution, being a contributor factor for the delaying ASR occurrence in some concrete structures (e.g. dams). Since there is presently no consensus on how to test for releasable alkalis in aggregates, a research program has been conducted to evaluate the factors that can affect the alkalis release in laboratory test conditions. This paper presents the results after 455 days evaluation of alkalis released by igneous aggregates with different grain sizes, in different alkaline solutions (Ca(OH)2, NaOH and KOH), in two different concentrations (1M and 0.7M) -with and without addition of saturated Ca(OH)2. The results obtained show that reducing the particle size of the aggregates leads to an increase of alkalis release to the solution, which is higher in the alkaline solutions of KOH and NaOH with saturated Ca(OH)2. The sodium extraction is higher in 0.7M KOH, while potassium is higher in 1M NaOH.